Flora and vegetation of the Dzhulaika Reserve in the Middle Dnipro (Dnieper) region of Ukraine - Goncharenko, Igor; Dvirna, Tetiana; Shevchyk, Vasyl; Solomakha, Igor; Senchylo, Olexandr; Polishko, Olexandr; Solomakha, Volodymyr; Drebot, Oksana (Biodiversity: Research and Conservation, 2024)
The botanical Dzhulaika Reserve, located in the middle part of the Dnipro (Dnieper) River valley, is a well-preserved area on the slopes of the Kremenchuk Reservoir in the forest-steppe zone of Ukraine. The taxonomic, biomorphological, and phytosociological structure of the plant communities was analysed, as well as the anthropophyte fraction, rare species, and habitats protected at the local, national, and international levels. The flora includes 657 species of vascular plants, of which 40 are protected at the regional level and 10 are included in the Red Data Book of Ukraine. The species composition, a brief description of vegetation, and lists of protected species and habitats are provided. The high floristic richness correlates with well-preserved vegetation, ranging from aquatic and wetland communities at the foothills to steppe and shrub-steppe communities and fragmented forests on the steep slopes of the Dnipro River. Taking into account the complete devastation of watersheds in the surrounding territories, this makes the study area a unique point of biodiversity in this part of Ukraine, so it requires appropriate protection measures and long-term monitoring.